A Pickering Emulsion Route to Swimming Active Janus Colloids. Issue 2 (1st December 2017) - Archer, Richard J.; Parnell, Andrew J.; Campbell, Andrew I.; Howse, Jonathan R.; Ebbens, Stephen J.
Abstract: The field of active colloids is attracting significant interest to both enable applications and allow investigations of new collective colloidal phenomena. One convenient active colloidal system that has been much studied is spherical Janus particles, where a hemispherical coating of platinum decomposes hydrogen peroxide to produce rapid motion. However, at present producing these active colloids relies on a physical vapor deposition (PVD) process, which is difficult to scale and requires access to expensive equipment. In this work, it is demonstrated that Pickering emulsion masking combined with solution phase metallization can produce self‐motile catalytic Janus particles. Comparison of the motion and catalytic activity with PVD colloids reveals a higher catalytic activity for a given thickness of platinum due to the particulate nature of the deposited coating. This Pickering emulsion based method will assist in producing active colloids for future applications and aid experimental research into a wide range of active colloid phenomena. Abstract : A Pickering emulsion synthesis of micrometer‐scale self‐motile catalytic Janus colloids is demonstrated. Compared to current production techniques involving metal evaporation, this new approach provides a low energy, scalable solution based synthesis. This method consequently enhances the viability of deploying motile colloids for real‐world applications, as well as facilitating lab‐scale investigation of collective active colloids behavior.